Early Predictors of Quality of Life among Patients with Type 2 Diabetes Mellitus in Southern Jordan - Faten Sameer Harb MSc, RN; Abdullah Algunmeeyn PhD, MSc, BSc; Mohammad Othman Abu Hasheesh PhD, MSc, RN; Faris El-Dahiyat PhD, MSc, BSc; Isra Alomar PhD, MSc, BSc; Abdullah Elrefae MD, BSc; Rani Ali Shnikat MD, BSc (SAGE Open Nursing)
Background Type 2 Diabetes Mellitus is highly prevalent worldwide and especially in Jordan, presenting a significant challenge in mitigating its associated complications, thereby emphasizing the need for effective management strategies. Aim The aim of the study was to investigate early predictors of quality of life (QOL) among patients with Type 2 Diabetes Mellitus in Southern Jordan, focusing on examining the relationships and associations between diabetes self-efficacy, glycemic control, and diabetes self-care with QOL. Methodology The study adopted a cross-sectional approach conducted within Southern Jordan, employing a convenience sampling method. Participants were chosen based on their availability and willingness to take part. The study encompassed a sample size of 204 patients diagnosed with type 2 diabetes. The study utilized the Diabetes Self-Management Questionnaire and the Diabetes Management Self-Efficacy Scale to assess diabetic patients’ self-care levels and self-efficacy, respectively. Data collection spanned from 1 February to 15 May 2023. Results Patients demonstrated suboptimal self-care and low self-efficacy. Significant positive correlations were found between QOL dimensions, self-management, and self-efficacy. Predictors for Type 2 Diabetes Miletus (T2DM) patients’ QOL were identified. For physical health, factors such as gender, comorbidities, age, occupation, location, self-care behaviors, and self-efficacy influenced QOL. Similar predictors were found for psychological, social, and environmental health dimensions, including gender, comorbidities, HbA1c levels, city of residence, marital status, and income, as well as self-care behaviors and self-efficacy. Conclusions The study findings underscore the importance of targeted interventions to improve the QOL for individuals with T2DMin Southern Jordan.